Optimized expression of Hfq protein increases Escherichia coli growth - Phuong N. L. VO; Hyang-Mi LEE; Jun REN; Dokyun NA (Journal of Biological Engineering, 2021)
Abstract Escherichia coli is a widely used platform for metabolic engineering due to its fast growth and well-established engineering techniques. However, there has been a demand for faster-growing E. coli for higher production of desired substances. Here, to increase the growth of E. coli cells, we optimized the expression level of Hfq protein, which plays an essential role in stress responses. Six variants of the hfq gene with a different ribosome binding site sequence and thereby a different expression level were constructed. When the Hfq expression level was optimized in DH5α, its growth rate was increased by 12.1% and its cell density was also increased by 4.5%. RNA-seq and network analyses revealed the upregulation of stress response genes and metabolic genes, which increases the tolerance against pH changes. When the same strategy was applied to five other E. coli strains (BL21 (DE3), JM109, TOP10, W3110, and MG1655), all their growth rates were increased by 18–94% but not all their densities were increased (− 12 − + 32%). In conclusion, the Hfq expression optimization can increase cell growth rate and probably their cell densities as well. Since the hfq gene is highly conserved across bacterial species, the same strategy could be applied to other bacterial species to construct faster-growing strains.